2001
DOI: 10.1046/j.1365-313x.2001.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Maize endosperm secretes a novel antifungal protein into adjacent maternal tissue

Abstract: SummaryA series of endosperm transfer layer-speci®c transcripts has been identi®ed in maize by differential screening of a cDNA library of transcripts at 10 days after pollination. Sequence comparisons revealed among this class of cDNAs a novel, small gene family of highly diverged sequences encoding basal layer antifungal proteins (BAPs). The bap genes mapped to two loci on chromosomes 4 and 10. So far, baphomologous sequences have been detected only in maize, teosinte and sorghum, and are not present in gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 35 publications
7
84
1
Order By: Relevance
“…Both BETL-1 and BETL-2, but especially the latter, were secreted into the maternal placento-chalazal region of the pedicel when expressed in the BETL (see arrowheads at the basal part of the endosperm in Figure 3A [magnified in 3B]); this observation was previously reported for BETL-2 by Serna et al (2001). Similarly, BETL-1 and BETL-2 expressed by the EETL accumulated on one side of the kernel, this time immediately under the pericarp (arrowheads in the EETL region, Figures 3A and 3C).…”
Section: The Expression Of Mrp-1 Induced the Tc Differentiation Procesupporting
confidence: 74%
See 1 more Smart Citation
“…Both BETL-1 and BETL-2, but especially the latter, were secreted into the maternal placento-chalazal region of the pedicel when expressed in the BETL (see arrowheads at the basal part of the endosperm in Figure 3A [magnified in 3B]); this observation was previously reported for BETL-2 by Serna et al (2001). Similarly, BETL-1 and BETL-2 expressed by the EETL accumulated on one side of the kernel, this time immediately under the pericarp (arrowheads in the EETL region, Figures 3A and 3C).…”
Section: The Expression Of Mrp-1 Induced the Tc Differentiation Procesupporting
confidence: 74%
“…Many of the TC-specific genes identified so far encode small hydrophilic proteins of unknown function, although there is increasing evidence that these proteins might be involved in the defense of the developing seed against mother plant-borne pathogens (Serna et al, 2001). In addition, it has been shown that MRP-1 can transactivate various TC-specific promoters, including those of BETL-1 and BETL-2 (Gó mez et al, 2002), Meg-1 (Gutié rrez-Marcos et al, 2004, and the TC-specific response regulator TCRR-1 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the data accurately reflect known patterns of protein accumulation (Fig. S1) (9,(17)(18)(19)(20)(21)(22). Examination of the data revealed that the majority of proteins are present in multiple tissues whereas only 1,203 are tissue-specific ( Fig.…”
Section: Significancesupporting
confidence: 62%
“…These genes showed CS scores in the given compartments ranging from 0.47 to 0.99. Third, we summarized previously reported in situ hybridization or promoter activity data for cell-specific genes from the literature (Hueros et al, 1995(Hueros et al, , 1999Magnard et al, 2000Magnard et al, , 2003Serna et al, 2001;Woo et al, 2001;Gómez et al, 2002Gómez et al, , 2009Gutiérrez-Marcos et al, 2004;Wisniewski and Rogowsky, 2004;Balandín et al, 2005;Massonneau et al, 2005;Muñiz et al, 2006Muñiz et al, , 2010Royo et al, 2014) and also found these genes to have a relatively high range of CS scores (0.51 to 0.99). Altogether, these comprise 44 genes showing cell-specific expression in the endosperm (Supplemental Table 6).…”
Section: Identification Of Gene Sets Specifically Expressed In Each Omentioning
confidence: 85%
“…The M18 module contained nearly all of the previously identified BETL-expressed genes (Hueros et al, 1995(Hueros et al, , 1999Cheng et al, 1996;Doan et al, 1996;Serna et al, 2001;Magnard et al, 2003;Gutiérrez-Marcos et al, 2004;Massonneau et al, 2005;Gruis et al, 2006;Muñiz et al, 2006Muñiz et al, , 2010Brugière et al, 2008;Gómez et al, 2009), including BETL-1, 3, 4, 9, and 10; BAP-1A, 1B, 2, 3A, and 3B; TCRR-1 and 2; and INCW2 (CELL WALL INVERTASE2), EBE-2 (EMBRYO SAC/BASAL ENDOSPERM-LAYER/EMBRYO-SURROUNDING REGION-2), IPT-2 (ISOPENTENYL TRANS-FERASE-2), and CC-8 (CORN CYSTATIN-8) (Supplemental Data Set 4). In addition, this module contained 11 of the 13 MEG genes (with MEG-4 and MEG-14 being the two exceptions) that have been identified in the B73 genome (Supplemental Data Set 4), including MEG-1, which is a BETL-specific gene that has been shown to be important for the development and differentiation of the BETL (Costa et al, 2012).…”
Section: Biological Processes Enriched In Coexpression Modules Of Thementioning
confidence: 99%